Internationalizing Islamic Higher Education in Indonesia: A Lesson Learned from Australia - Sibawaihi Sibawaihi; Dwi Ratnasari; Sri Purnami; Melanie Brooks (Jurnal Pendidikan Islam, 2025)
Internationalization plays a crucial role in enhancing the quality and global recognition of Islamic higher education institutions in Indonesia. This study investigates how these institutions implement internationalization by drawing insights from the experience of Monash University in Australia. Using a qualitative case study approach, data were collected through interviews and document analysis. The findings indicate that while Islamic higher education institutions have implemented key aspects of internationalization, there is still room for improvement. Institutions must continuously enhance educational quality while maintaining their unique identity to attract international students. Greater autonomy in financial and administrative management is necessary to align Islamic universities with other leading public institutions. Policy support from the government is essential in ensuring institutional autonomy and protecting human resource rights without excessive intervention. Seeking international accreditation through relevant accrediting bodies is also critical in strengthening global competitiveness. These findings highlight the need for strategic efforts by university leaders, government, and stakeholders to advance the internationalization agenda in Islamic higher education. Strengthening institutional autonomy, improving quality standards, and achieving international accreditation will contribute to greater global engagement and recognition of Islamic universities in Indonesia.